Counseling on Clean and Healthy Living Behaviors (PHBS) at State Primary School 101900 Lubuk Pakam - Wulan, Sri; Pardede, Desika Wali (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
Implementing Clean and Healthy Living Behavior (PHBS) among elementary school children is very important to prevent disease, build healthy habits from an early age, improve learning achievement, reduce absenteeism, and create a clean school environment. With continuous education and active participation from all parties, including teachers, students and parents, PHBS can become a strong foundation for children's health and well-being, both now and in the future. The aim of this counseling is to form clean and healthy living habits from an early age in children at SD Negeri 101900 Lubuk Pakam. With a comprehensive and continuous educational approach, it is hoped that children can internalize clean and healthy living behavior as part of their daily routine. The method used is a pretest before presenting the material, then continuing with an explanation or presentation of material about the importance of PHBS and practicing it directly, such as washing hands, brushing teeth, environmental cleanliness, after that, a posttest or observation of the implementation of PHBS is carried out again, with 60 counseling participants. counseling place at SD Negeri 101900 Lubuk Pakam. From the results of the activity, it can be seen that before the counseling was carried out, the majority of participants had little knowledge about PHBS and after the counseling was carried out the majority had good knowledge and the participants also understood the importance of PHBS and were able to practice it correctly. It was concluded that it is important to carry out PHBS counseling or explanations at SD Negeri 101900 Lubuk Pakam to increase knowledge and change behavior and create an environment that supports health and well-being for the entire school community.